2021
DOI: 10.1086/716853
|View full text |Cite
|
Sign up to set email alerts
|

BaYaka Adolescent Boys Nominate Accessible Adult Men as Preferred Spear Hunting Models

Abstract: Humans are selective social learners. In a cultural landscape with many potential models, learners must balance the cost associated with learning from successful models with learning from accessible ones. Using structured interviews, we investigate the model selection biases of Congolese BaYaka adolescent boys learning to hunt with spears (n=24, mage=15.79 years, range: 12-20 years). Results from Social Relations Models suggest that adolescents nominated accessible adult men (closely related kin and neighbors)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Our previous research demonstrated that while spear hunting is widely practised by BaYaka, they consider it to be an especially complex task [22]. We found that most spear hunting knowledge transmission reportedly occurred from fathers and other closely related male kin, primarily via teaching [22,46]. The present study builds on this work by investigating the types of teaching that contribute to BaYaka spear hunting knowledge acquisition.…”
Section: Ethnographic Backgroundmentioning
confidence: 80%
See 3 more Smart Citations
“…Our previous research demonstrated that while spear hunting is widely practised by BaYaka, they consider it to be an especially complex task [22]. We found that most spear hunting knowledge transmission reportedly occurred from fathers and other closely related male kin, primarily via teaching [22,46]. The present study builds on this work by investigating the types of teaching that contribute to BaYaka spear hunting knowledge acquisition.…”
Section: Ethnographic Backgroundmentioning
confidence: 80%
“…All models included a fixed effect for pupil age in years estimated using the methods outlined in [46,55], and a fixed effect for pupil experience estimated as the total number of prey previously speared by the pupil (log-transformed as log( x + 1)). To facilitate estimation, these variables were z- score standardized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dutch, British, Italian, and Singaporean adolescents favored the opinions of their peers when complying with rules (Westhoff et al, 2020), subjectively evaluating risk (Knoll et al, 2017) and sharing (Ruggeri et al, 2018). Yet in other areas—such as in estimating tasks where objectively correct responses were possible (Molleman et al, 2019), hunting (Lew‐Levy et al, 2021), and acquiring innovations (Hewlett, 2021)—Indian, BaYaka (Republic of the Congo), Aka (Central African Republic), and Chabu (Ethiopia) adolescents preferred to learn from adults. Together, these findings suggest that adolescent learning depends on the domain being transmitted.…”
Section: Peer Learning Is Selective and Changes Throughout Developmentmentioning
confidence: 99%